Effect of digital elevation model’s resolution in producing flood hazard maps - J.L. Ogania; G.R. Puno; M.B.T. Alivio; J.M.G. Taylaran (Global Journal of Environmental Science and Management)
Flooding is one of the most devastating natural disasters occurring annually in the Philippines. A call for a solution for this malady is very challenging as well as crucial to be addressed. Mapping flood hazard is an effective tool in determining the extent and depth of floods associated with hazard level in specified areas that need to be prioritized during flood occurrences. Precedent to the production of maps is the utilization of reliable and accurate topographic data. In the present study, the performance of 3 digital elevation models having different resolution was evaluated with the aid of flood modeling software such as hydrologic engineering centre-hydrologic modeling system and hydrologic engineering centre-river analysis system. The two-dimensional models were processed using three different digital elevation models, captured through light detection and ranging, interferometric synthetic aperture radar, and synthetic aperture radar technologies, to simulate and compare the flood inundation of 5-, 25- 100-year return periods. The accuracy of the generated flood maps was carried out using statistical analysis tools - Overall accuracy, F-measure and root-mean-square-error. Results reveal that using light detection and ranging–digital elevation model, the overall accuracy of the flood map is 82.5% with a fitness of 0.5333 to ground-truth data and an error of 0.32 meter in simulating flood depth which implies a promising performance of the model compared to other data sources. Thus, higher resolution digital elevation model generates more accurate flood hazard maps while coarser resolution over-predicts the flood extent.